2010
DOI: 10.1093/nar/gkq1127
|View full text |Cite
|
Sign up to set email alerts
|

eIF4G stimulates the activity of the DEAD box protein eIF4A by a conformational guidance mechanism

Abstract: The activity of eIF4A, a key player in translation initiation, is regulated by other translation factors through currently unknown mechanisms. Here, we provide the necessary framework to understand the mechanism of eIF4A’s regulation by eIF4G. In solution, eIF4A adopts a defined conformation that is different from the crystal structure. Binding of eIF4G induces a ‘half-open’ conformation by interactions with both domains, such that the helicase motifs are pre-aligned for activation. A primary interface acts as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
137
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 39 publications
16
137
0
Order By: Relevance
“…However, the two core domains do not close completely, as observed for eIF4AIII in the EJC 89,91 . The eIF4G-induced, half-open form of eIF4A promotes RNA binding and also accelerates phosphate release, which is presumably the rate-limiting step in the ATPase cycle for eIF4A 91 . These findings are consistent with the well-documented stimulation of the RNA-dependent ATPase activity of eIF4A by eIF4G 85 .…”
Section: Nuclear Specklesmentioning
confidence: 82%
“…However, the two core domains do not close completely, as observed for eIF4AIII in the EJC 89,91 . The eIF4G-induced, half-open form of eIF4A promotes RNA binding and also accelerates phosphate release, which is presumably the rate-limiting step in the ATPase cycle for eIF4A 91 . These findings are consistent with the well-documented stimulation of the RNA-dependent ATPase activity of eIF4A by eIF4G 85 .…”
Section: Nuclear Specklesmentioning
confidence: 82%
“…Interestingly, cofactors are often RNA-binding proteins (19)(20)(21)(22)(23)(24)(25). We and others therefore postulated that these cofactors could also function to provide specificity for DEAD-box and DEAH-box proteins (1, 18).Ded1 and eIF4A, two of the best-studied DEAD-box proteins (19,24,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38), have known binding cofactors: Gle1 and eIF4G, respectively. Because Ded1 and eIF4A both function in translation initiation, a process that requires the recognition of many diverse mRNAs, sequence specificity for these particular DEADbox proteins may be undesirable.…”
mentioning
confidence: 99%
“…We have previously validated our correction procedure and have shown that it yields corrected FRET efficiencies that reflect correct intermolecular distances (see Ref. 24 for a detailed description).…”
Section: Methodsmentioning
confidence: 99%